Perbandingan Pertumbuhan Bayi dengan Pemberian ASI Ekslusif dan Non Ekslusif - Nurbaiti Br. Singarimbun; Suharni Pintamas Sinaga; Selli M. Pasaribu (Journal of Pharmaceutical and Health Research, 2023)
Nutrition is a nutritional intake that plays an important role during the period of growth and development in infants. The nutrition that babies aged 0-6 months need comes from exclusive breastfeeding. About 13% of infant mortality can be reduced through exclusive breastfeeding. The study aims to determine the comparison of infant growth with exclusive and non-exclusive breastfeeding. The research method used was a descriptive design with a population of 50 infants aged 6 months at the Bawomataluo Health Center. The results of the analysis showed that the average growth of babies who were given exclusive breastfeeding based on body weight was 6.11, body length was 65.68 and head circumference was 42.72. While the average growth of babies with non-exclusive breastfeeding based on body weight was 4.56, body length was 56.56 and head circumference was 37.96. Differences in infant growth based on body weight, body length and head circumference as well as infant development between exclusively and non-exclusively breastfed infants (p = 0.000 <0.05). The conclusion shows that the growth of babies at the Bawomataluo health center with exclusive breastfeeding is better than non-exclusive.